PENGARUH EDUKASI SEKS MELALUI APLIKASI VIDEO ANIMASI TERHADAP PENGETAHUAN DALAM MENCEGAH PELECEHAN SEKSUAL - Zalni, Rummy Islami; Mardianti, Riska; Juwita, Ratna; Aristi, Tiffany Atia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Based on data from the Riau Province P2TP2A UPT 2021, sexual crime cases handled by the Riau Province P2TP2A UPT in the last 3 years from 2016 to 2018, there were 49 cases of sexual crimes against women and children in Pekanbaru City, which showed that in 2016 there were 11 cases, then in 2017 there were 18 cases, and in 2018 it increased again by 20 cases of sexual crimes. Providing sexual education at an early age will have an impact on children's sexual health when they are adults. The way to prevent sexual harassment is by providing education through animation media. Animation media is the movement of an object or image so that it can change position. The purpose of this study was to determine the effect of sex education through animated video applications on knowledge in preventing sexual harassment from an early age. This study uses a One Group Pretest Posttest design. Data collection was carried out using a questionnaire sheet. The sample was determined by the total sampling method of 35 respondents. The result of the T-test p-value is 0.000 because the value of 0.000 is smaller than <0.05, so it can be concluded that there is an effect of sex education through animated video applications on knowledge in preventing sexual harassment at SDN 04 Lubuk Dalam, Siak Regency so that H0 is rejected. It is recommended that everyone use animated videos to increase knowledge in preventing sexual harassment.Keywords: animated videos, knowledge, sexual harassment